2021
DOI: 10.1007/s00277-021-04568-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucositis in patients with acute myeloid leukemia treated with allogeneic hematopoietic stem cell transplantation in relation to the conditioning used prior to transplantation

Abstract: This study was designed to investigate the frequency and severity of oral mucositis in patients with acute myeloid leukemia after allogeneic hematopoietic cell transplantation, in relation to the type of conditioning used. Eighty patients diagnosed with acute myeloid leukemia were assigned to two groups based on the conditioning regimen used before transplantation. The intensity of oral inflammatory lesions induced by chemotherapy (oral mucositis) was evaluated according to a 5-point scale recommended by World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the Nagasaki Transplant Group, the conditioning intensity is determined by the consensus of the Center for International Blood and Marrow Transplant Research criteria [22,23]. Several reports have shown that the appearance of OM with chemotherapy depends on the dose and type of chemotherapy and that the incidence of OM is higher with MAC than RIC regimens in patients undergoing HSCT [24,25]. These findings are in agreement with our results.…”
Section: Discussionsupporting
confidence: 90%
“…In the Nagasaki Transplant Group, the conditioning intensity is determined by the consensus of the Center for International Blood and Marrow Transplant Research criteria [22,23]. Several reports have shown that the appearance of OM with chemotherapy depends on the dose and type of chemotherapy and that the incidence of OM is higher with MAC than RIC regimens in patients undergoing HSCT [24,25]. These findings are in agreement with our results.…”
Section: Discussionsupporting
confidence: 90%
“…In the Nagasaki Transplant Group, the conditioning intensity is determined by the consensus of the Center for International Blood and Marrow Transplant Research criteria [24,25]. Several reports have shown that the appearance of OM with chemotherapy depends on the dose and type of chemotherapy and that the incidence of OM is higher with MAC than RIC regimens in patients undergoing HSCT [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies focus on individual cancer types; thus, it is difficult to generalize OM as a common side effect of therapy in patients with cancer [ 6 , 8 , 15 , 19 ]. We recruited several patients with leukemia and head and neck carcinoma in an attempt to provide a broader representation of patients with OM.…”
Section: Discussionmentioning
confidence: 99%
“…OM occurs as a common side effect in patients with cancer receiving chemotherapy (CTx) and radiotherapy (RT), which can be severe and impede the quality of life [ 2 4 ]. More than 75% of the patients with leukemia undergoing CTx and bone marrow transplantation (BMT) experience OM [ 5 , 6 ], and > 40% of those receiving RT experience ≥ grade 3 OM [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%